2006
DOI: 10.1007/s00348-006-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

Solid transport measurements through image processing

Abstract: The paper describes a novel technique which enables evaluation of sediment fluxes on the upper layer of a granular bed by means of separate measurements of concentration and velocity of the moving particles. Specific elaboration techniques based on digital image processing were applied to films of the solid fluxes, allowing for automatic measurement. Sediment concentration was measured via a technique based on image subtraction and following proper filtering procedures, while grain velocity was measured by Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 16 publications
3
45
0
2
Order By: Relevance
“…Concerning comparable velocities, it has already been reported that particle velocity is only weakly dependent on the bed shear stress at least for saltation (Niño et al, 1994) or low concentration bedload (Radice et al, 2006), which is consistent with our conditions in the upper part of the profile. Above y* = 1, a reverse trend occurs, the velocity values are comparable while the concentration of N10-20 becomes much higher than that of N10-6.…”
Section: Depth Profilessupporting
confidence: 93%
“…Concerning comparable velocities, it has already been reported that particle velocity is only weakly dependent on the bed shear stress at least for saltation (Niño et al, 1994) or low concentration bedload (Radice et al, 2006), which is consistent with our conditions in the upper part of the profile. Above y* = 1, a reverse trend occurs, the velocity values are comparable while the concentration of N10-20 becomes much higher than that of N10-6.…”
Section: Depth Profilessupporting
confidence: 93%
“…Keshavarzy & Ball, 1999;Spinewine et al, 2003;Radice et al, 2006). In this study of suffusion, the velocity of the mobile particles is of secondary importance.…”
Section: Introductionmentioning
confidence: 97%
“…Such techniques are used to investigate movement of individual particles, for example colloid transport in porous media (Ochiai et al, 2006) and entrainment from a sediment bed (Radice et al, 2006;Wang et al, 2009), as well as the movement of collections of particles using particle image velocimetry (PIV) (e.g. White & Bolton, 2004;Slominski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made in suspended sediment turbulencerelated issues and more recently in bedload research. Image analysis has been used in laboratories, more rarely in the field (Drake et al 1988), to measure for instance concentrations or number of particles (Radice et al 2006), grain size distributions and mass flux (Frey et al 1993Graham et al 2005;Zimmermann et al 2008), and particle velocities or trajectories. Tracking a single detected particle is relatively easy, and a number of authors have used image analysis to measure the trajectory of a particle in saltation (Hu and Hui 1996;Niño et al 1994, Lee et al 2000Ancey et al 2002) or in the rolling regime (Ancey et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Drake et al (1988) performed field tests with natural sediments, extracting information from the images by hand. Radice et al (2006) evaluated sediment fluxes from above. The concentration was measured by segmenting subtracted images, a technique already used by Keshavarzy and Ball (1999).…”
Section: Introductionmentioning
confidence: 99%